If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(s + -7) = -92 Reorder the terms: 8(-7 + s) = -92 (-7 * 8 + s * 8) = -92 (-56 + 8s) = -92 Solving -56 + 8s = -92 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '56' to each side of the equation. -56 + 56 + 8s = -92 + 56 Combine like terms: -56 + 56 = 0 0 + 8s = -92 + 56 8s = -92 + 56 Combine like terms: -92 + 56 = -36 8s = -36 Divide each side by '8'. s = -4.5 Simplifying s = -4.5
| 3x-4=x-10 | | 3x+4+x+20=180 | | 8x+6y=120 | | S^2-s-12=0 | | 8(2l+2)=32 | | 4x+(-7x)=9 | | 3(a-5)=54 | | -3x+7+2x=5 | | 8x-4+12+6x=180 | | 50x^2+40x-45=0 | | 48-92+67=y | | 25x-4x+y=36 | | (2x-5)(3x^2+3x-1)= | | p-4/11=29/11 | | (x+8)-x-(5-6)=15 | | X^3-5x-14x=0 | | 5c-(-32)=87 | | 4-6x=3y | | 3w^2-12w+16=0 | | 9-3x+5=2x+4 | | 10+5=515 | | 4n+2=7n-13 | | 24-3c=3 | | x^2-27x+1=0 | | 13-13=2w | | 22+3n=88 | | 21=x+7x+5 | | T+8.3=2.67 | | 8(y+2)=72 | | -6x-8+2x=-8 | | -9+3t+2t^2=0 | | 4q+8=16 |